A Classification Model for Managers by Competencies: A Case Study in the Construction Sector. (12th November 2017) - Famá, Camila Campos Gómez; Alencar, Luciana Hazin
Abstract : Many companies have difficulties in filling managerial positions. This is because there is a lack in understanding of the competencies that a manager must have. This is as true for those responsible for selecting managers as it is for the employee who aspires to be a manager. Furthermore, the construction industry seeks to appoint managers who are likely to excel in several different managerial roles. However, currently, there is no model that classifies managers by the different competencies they need to perform specific functions. This paper presents how a nonordered classification method was applied in a construction company in order to select managers for different roles. While no manager is considered to be more important than any other, they nevertheless need to have different competencies that match those needed for the job assigned to them. The model also serves as a guide for evaluating whether or not those already in or being considered for a managerial position have the competencies required.